The Effect of Administering Lemon Basil (Ocimum sanctum) Leaves on FSH and LH Estrogen Levels and Size of Ovarian Antral Follicle in Female Balb/C Mice - Maryanti, Sri; Nasihun, Taufiqurrachman; Amalia, Helfi (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2019)
INTRODUCTION: Ocimum sanctum have been proven effective in decreasing Follicle Stimulating Hormone (FSH), Luteinizing Hormone (LH) levels, and sperm number, and also increase male testosterone levels. However, so far no evidence has been found on the effect of Ocimum sanctum leaves on the levels of estrogen, FSH, LH, and the size of ovarian anthral follicles. OBJECTIVES: To evaluate the effect of Ocimum sanctum leaves on estrogen, FSH, LH and the size of antral follicle of female Balb/C mice.METHODS: In the post test only control group design, 12 female Balb/C mice were assigned into 2 groups. The treatment group (OS-G) was given 0.08 gram of ocimum sanctum leaves, three times a day for 30 days and the control group (C-G) received no ocimum sanctum. Estrogen, FSH anduLH levels wereumeasured on the 30th day, the mice were sacrificed and taken up by their ovaries. HE preparationsuwere then madeuand HE was performed, and the size of the antral follicle of the ovary was measured .RESULTS: Mann Whitney analysisuindicateduthat estrogen and FSH levels in OS-G group were significantly higher compared to that of C-G group, p<0.05. Based on independent t-test, the level of LH in OS-G was significantly higher than that of C-Gugroup, p><0.05. On the contrary, uthe size of ovarianuanthralufollicle in OS-Guwas smaller than that of C-Gugroup, p><0.05. CONCLUSION: Ocimum sanctum increased the levels of estrogen, FSH, LH and decreased the size of ovarian antral follicle in female of Balb/C mice.>